Sadgurucaritra : Sahajānandī jīvana-yajña - Vyāsa, Tribhuvana, 1888-1975 (SAMP early 20th-century Indian books project, 1923)
Biography of Swami Sahajānanda, 1781-1830, founder of the Swami-Narayanis, sect in Hinduism.